Evaluation of quality of life pre- and post-vestibular rehabilitation in patients with benign paroxysmal positional vertigo associated with Meniere's disease - Socher, Dayra Dill; Socher, Jan Alessandro; Azzi, Viviane Jacintha Bolfe (International Archives of Otorhinolaryngology, 2012)
Introduction: Vertigo is a symptom that impacts the patients' quality of life and may force them to cease performing activities of daily living. Here, we discuss benign paroxysmal positional vertigo (BPPV) and Meniere's disease (MD), which show exacerbated symptoms when they appear in association. Vestibular rehabilitation (VR) is an effective treatment in reducing vertigo, especially in conjunction with other therapies.Aim: To evaluate the quality of life of patients with BPPV and MD before and after VR.Method: We conducted a descriptive observational qualitative and quantitative case study with 12 patients aged 35 to 86 years. All patients diagnosed with BPPV and MD received treatment in the ENT clinic. The Brazilian DHI questionnaire, which assesses the quality of life with a focus on physical, emotional, and functional aspects, was used for data collection, and was completed by patients before the first session and after the fifth session of VR. Data were tested using the Shapiro-Wilk normality test, followed by Wilcoxon, Friedman, and Spearman correlation tests (p < 0.05).Results: There were significant improvements in scores for all aspects, with median changes ranging from 12 to 0 in the physical, 6 to 1 in the emotional, and 11 to 1 in the functional aspect. There were no correlations between the scores and sample characteristics.Conclusion: VR was an effective method for the treatment of patients with BPPV and MD; it improves quality of life and shows the maximal influence on physical aspect scores, regardless of age or gender.
Keywords: quality of life; vertigo; meniere disease; rehabilitation